Analisis Yuridis Pemajakan Capital Gain Aset Kripto Indonesia Singapura dan Mitigasi Capital Flight - Farras Eknu Albin; Risqi Budi; Christian Bagas; Rois Faisal; Nabil Ivander; Moh. Imam Gusthomi (JURNAL PENELITIAN SERAMBI HUKUM, 2026)
The development of cryptocurrency as a digital investment instrument has created new challenges for national taxation systems, particularly regarding the taxation of capital gains and the potential risk of capital flight. Indonesia, through Minister of Finance Regulation Number 68/PMK.03/2022, has regulated the taxation of crypto asset transactions, while Singapore adopts a relatively more flexible policy toward digital asset investment gains. This study aims to analyze the comparative regulation of cryptocurrency capital gains taxation in Indonesia and Singapore and its implications for potential capital flight. This research employs a normative juridical method using statutory and comparative approaches. The findings indicate that differences in taxation regimes between Indonesia and Singapore may influence investors’ decisions in determining the location of digital asset transactions. Therefore, an adaptive and competitive taxation policy is required to maintain legal certainty while preventing capital flight in the digital economy era.